An investigation of the role of trust in virtual project management success. (21st December 2011) - Mumbi, Chanda; McGill, Tanya
Virtual project teams introduce new challenges for project managers tasked with the job of delivering project success. One such challenge is the development and maintenance of trust within the virtual environment. The paper explores the role that trust plays in virtual project teams and investigates how trust influences project outcomes. A model of trust in the virtual team environment is proposed and tested using data collected from a survey of members of the Project Management Institute. Analysis of the data showed that virtual team trust predicted project success, however swift trust and perceived traditional experience did not have any influence on virtual team trust. Based on the results of the study, the paper explores and recommends strategies to develop and maintain trust to a level that promotes the success of virtual team projects.